Differences in the influence of self-regulated learning levels on enhancing students’ mathematical reasoning abilities - Maulida, Aya Shofia; Wahyudin, Wahyudin; Turmudi, Turmudi; Nurlaelah, Elah (Universitas Sebelas Maret, 2024)
Self-regulated learning allows students to organize, monitor, and evaluate their learning process, which has a positive impact on mathematical reasoning abilities. This research aims to analyze and describe the differences in the influence of the level of self-regulated learning on students' mathematical reasoning abilities. The research method used is quantitative, which allows the collection and analysis of numerical data to identify patterns and relationships. The method's goal is to measure variables, test hypotheses, and make generalizations from a sample to a broader population. The sample for this research was eighth-grade students in Bandung. The research instrument is in the form of 30 questionnaire statements about students' self-regulated learning. The research hypothesis, there are differences in the influence of self-regulated learning levels on enhancing students’ mathematical reasoning abilities. The research results show that there are differences in the influence of the level of self-regulated learning on students' mathematical reasoning abilities. In addition, variations were found in the influence of the level of self-regulated learning on enhancing students' mathematical reasoning abilities. This research concludes that the level of self-regulated learning plays an important role in enhancing students' mathematical reasoning abilities.